Economic Evaluation and Sensitivity Analysis of Methanol Plant from Glycerol - Meilani Kusuma Wati; Elmi Sunarya; Nada Zafirah; Hari Rionaldo; Zulfansyah Zulfansyah (Jurnal Informasi, Sains dan Teknologi, 2024)
Methanol plant from glycerol is a good prospect in Indonesia. Until 2021, methanol is only supplied by one methanol producer located in East Kalimantan, namely PT. Kalimantan Timur with a production capacity of 660,000 tons/year. Therefore, the methanol plant from glycerol has a very important meaning for the acquisition of foreign exchange as well as employment. This article presents an economic evaluation of a methanol plant from glycerol with a capacity of 40,000 tons/year. Profitability analysis calculation is done by two methods, the method that do not consider the time value of money and the method that consider the time value of money. The results of the method that do not consider the time value of money obtained ROI value (before tax) 34.62%, ROI value (after tax) 24.24%, and the value of PBP 2.98 years. Using the method that consider the time value of money, the NPW value was Rp. 1,458 billion and the DCFRR / IRR was 39.25%. The sensitivity analysis also deserves to see the effect of the factor that influence the economic viability, and provide more information for the optimization of Methanol production.